Comparative study of vicryl polyglactin (910) versus chromic catgut for episiotomy repair - Kaur, Nazamdeep; Kaur, Amrit P.; Manku, Harpoonam; Kaur, Kiranjeet (International Journal of Research in Medical Sciences, 2024)
Background: The aim of the study was to compare two different absorbable suture materials, namely vicryl rapide (no. 2-0) and chromic catgut (no.1-0) for episiotomy repair and evaluate their outcomes related to short term maternal post-partum morbidity. Methods: The prospective randomized comparative study was conducted in the department of obstetrics and gynecology, Bebe Nanki Mother and Child Care Centre, Amritsar, for a period of 1 year, with 200 pregnant females admitted in the labour room who needed episiotomies for vaginal delivery and were randomly allocated for episiotomy repair with either vicryl polyglactin (910) (no. 2-0) or chromic catgut (no.1-0) with 100 patients in each group and various parameters like pain, swelling, tenderness, dyspareunia, wound discharge and dehiscence were assessed in each group at 24-48 hours, 10-14 days and 6 weeks postpartum. Results: The sociodemographic characteristics were comparable in both groups. Compared to chromic catgut, the vicryl rapide group was associated with lesser pain (7% versus 21%), feeling of stitches (20% versus 38%) and swelling and tenderness (4% versus 12%). There was significantly less wound disruption (3% versus 12%), feeling of stitches (11% versus 21%) and wound discharge (1% versus 7%) in vicryl rapide group at 10-15 days. Residual pain and dyspareunia were also less in vicryl group at 6 weeks. Conclusions: It can be concluded that vicryl rapide is a superior suture material than chromic catgut for repair of episiotomy as it results in lesser complications and improved wound healing.